First evidence of sucrose biosynthesis by single cyanobacterial bimodular proteins - Martínez Noël, Giselle María Astrid (2013)
The net synthesis of sucrose (Suc) is catalysed by the sequential action of Suc-phosphate synthase (SPS) and Suc-phosphate phosphatase (SPP). SPS and SPP from Anabaena sp. PCC 7120 (7120-SPS and 7120-SPP) define minimal catalytic units. Bidomainal SPSs, where both units are fused, occur in plants and cyanobacteria, but they display only SPS activity. Using recombinant proteins that have fused 7120-SPS and 7120-SPP, we demonstrated that they are bifunctional chimeras and that the arrangement 7120-SPS/SPP is the most efficient to catalyse the sequential reactions to yield Suc. Moreover, we present the first evidence of a bidomainal SPS present in the cyanobacterium Synechococcus elongatus PCC 7942 with both, SPS and SPP activity.